SANLÍ MÁKÁN SHARAYATÍNDA JASLAR SANASÍNDA ǴALABALÍQ SANASÍZLÍQ JAǴDAYLARÍNÍŃ QÁLÍPLESÍWÍ - Mambetnazarova, Mexribanu Tolıbaevna (SCIENCE and SOCIETY, 2026)
The article examines the socio-psychological characteristics of the formation of mass unconsciousness among youth in the digital environment, focusing on the influence of social networks and algorithmic content on critical thinking and decision-making.